Hubungan Komunikasi SBAR saat Handover dengan Penerapan Patient Safety di Rumah Sakit Bakti Timah Karimun - Elvi Murniasih; Utari Christya Wardhani; Maria Maria (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: The application of patient safety goals is an effort made by hospitals to improve the quality of health services. Handover activities that are not accompanied by effective communication can cause errors that can harm the patient. Recommendations from WHO require nurses to improve communication patterns, especially when carrying out handovers, namely by using SBAR communication which consists of Situation, Background, Assessment and Recommendation. Based on the data summary of reported incidents that occurred in the hospital as many as 20 incident cases in the past year, including cases of KTD, KNC, KTC and KPCS. From these incidents, there were 6 cases related to miscommunication during handovers. Some nurses still do not apply the SBAR communication method when carrying out handovers, resulting in cutting/lagging of the information provided and resulting in incidents. Objective:to determine the reltionshipbetween SBAR Communication during handover and the implementation of patient safety at Bakti Timah Karimun Hospital. Methods: This research is quantitative with a cross-sectional approach. The population of this study were all inpatient nurses at Bakti Timah Karimun Hospital with total sampling, which consisted of 63 respondents. Results: showed that 41 respondents (65%) used SBAR communication during handovers in the good category and implemented patient safety. Conclusion:This means that the implementation of SBAR communication during the handover is good but not optimal because there are still 35% who have not implemented it. Based on the chi square test, there is a relationship between SBAR communication during handover and the application of patient safety (p=0.000 <0.05). Suggestion:, it is expected that nurses can carry out SBAR communication during handovers effectively so that they can implement patient safety optimallyKeywords : Newbron, Skin wrap, hypothermia.